Perceptions of Possibilities: An Exploration of Transatlantic Collaboration. (2nd January 2021) - Harris, Heather; Hatcher, Sarah Junk; Kampschulte, Lorenz
ABSTRACT: The act of co-authoring an article across two languages (German and English) and three institutional contexts (a large science and technology museum, a university-based small art museum and a university-based small anthropology museum) led to numerous instances in which the meaning of particular terms had to be both articulated and negotiated to ensure understanding. This was uniquely important given that the article being written was about collaboration and cooperation. The process for doing so took place in the digital margins of our shared document, creating a dataset that could be interrogated through further conversation and careful analysis. While we recognized that translation work was happening, this analysis led us to understand how translation and collaboration are conjoined. We argue that all collaborations require acts of translation as participants establish shared understandings, build relationships, and decenter personal, cultural, and institutional assumptions.